Analysis of Forensic Cases in Patients Aged 65 and Older Presenting to the Emergency Department - Buyurgan, Çağrı Safa; Yarkaç, Akif; Bozkurt, Seyran; Köse, Ataman; Dokgöz, Halis; Güldür, Buğrahan; Koyuncu, Rohad Sadık; Orekici Temel, Gülhan (The Bulletin of Legal Medicine, 2025)
Objective: This study aims to examine the preparedness and operational capacities of local governments in Turkey against Chemical, Biological, Radiological, and Nuclear (CBRN) threats. It seeks to identify current practices, highlight institutional strengths and weaknesses, and offer recommendations for more effective coordination and response strategies. Methods: A qualitative research design was employed, using descriptive analysis to interpret data gathered through literature review and field observations. The study focused on examining the legal regulations, operational protocols, and preparedness strategies of local authorities and their affiliated bodies concerning both actual and potential CBRN threats. Results: The research reveals that institutions such as AFAD, the Turkish Atomic Energy Authority, and the Ministry of Health guide the development of localized CBRN procedures. Fire departments under local governments serve as primary operational units in this domain. While some provinces demonstrate strong preparedness, discrepancies in training, resources, and inter-agency coordination persist. Field observations also indicated that although joint response mechanisms exist, their implementation varies. Civil society organizations contribute to enhancing coordination, and national exercises such as the Turkey Disaster Response Plan are used to evaluate and improve institutional readiness. Conclusion: Despite the high-risk nature of CBRN incidents prompting faster institutional responses, gaps remain in clearly assigning authority in hot zones and in selecting appropriate intervention strategies. These challenges highlight the need for standardized protocols and clearer inter-agency frameworks to ensure a more unified and effective CBRN response across local governments.